The Advantage of Yeast Saccharomyces Cerevisiae for Livestock - Riza Zainuddin Ahmad (Indonesian Center for Animal Research and Development, 2005)
Saccharo nyces cerevisiae is a yeast that is useful for human and animal . It can be used for producing food and for biotechnology of industrial purposes . Recently. it is used as probiotic and immunostimulant to improve livestock productivity and health . Research results indicate that the utilization of S . cerevisiae as feed additive in animal feed has a positive correlation to the body weight gain of the animal . This paper describes the importance of S. cerevisiae in improving livestock productivity and health. Key words : S. cerevisiae, probiotic, immunostimulant, livestock